Government transparency impacts and unintended consequences - Erkkila, Tero (Public sector organizations, 2012)
Transparency has become a global concept of responsible government. This book argues that the transnational discourse of transparency promotes potentially contradictory policy ideas that can lead to unintended consequences. It critically examines whether or not increased transparency really leads to increased democratic accountability.